Digitalization of Tourism Village Branding: Optimizing the Potential of Mangrove Forests - Yoraeni, Ani; Marullah, Marullah; Asep, Asep; Saputra, Ridwan; Ari Saputro, Ridho (Universitas Nurul Jadid, 2025)
The community service program in the Sedari Village Mangrove Forest was implemented to address the limited utilization of digital technology in tourism promotion. Prior to the program, tourist visits averaged fewer than 60 per month, while the village’s promotional account received fewer than 10 interactions per post, indicating weak digital recognition and the need for stronger branding. This program aimed to strengthen community capacity through an integrated approach encompassing information technology, branding, and digital promotion. Information technology facilitated content management, branding established a distinctive identity for the mangrove tourism village, and digital promotion effectively disseminated this identity across online platforms. Key activities included developing an official tourism website, providing mentoring on branding that emphasized local characteristics, and collaborating with influencers to expand market reach. The results demonstrated that the website attracted 5,600 visits within two months of launch, while branding support enhanced partners’ ability to design logos, brochures, and social media content. Furthermore, influencer collaboration significantly increased engagement and improved the village’s public image. Overall, the program contributed to community-based sustainable tourism by improving digital literacy, fostering active community participation, creating additional income opportunities, and enhancing awareness of mangrove conservation.